2021
DOI: 10.1590/2447-536x.v27i3.2372
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest physiology of cut flowers

Abstract: The longevity of cut flowers is limited by their ephemeral nature and by multiple stresses. Impairment in water uptake, depletion of stored carbohydrates, increases in both respiratory activity and ethylene production are signatures of flower senescence. A wide range of techniques is available to extend flower preservation, including the use of flower preservative solutions, ethylene action inhibitors, growth regulators, and control of temperature and flower dehydration. The use of sucrose in pulsing solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…In cut flowers, the carbohydrate reserves may increase the longevity potential of the flowers (Mattos et al, 2018). For some species, the carbohydrates present in the flower can support an increase in postharvest durability of the flower, while in other species; they are not enough to supply the metabolism of the flowering stems after cutting (Costa et al, 2021). Thus, the maintenance of the sugar content in the Red Torch ginger inflorescences coated with 6% starch compared to the other treatments (0, 2%, 4%) shows the efficiency of this coating in delaying the consumption of reserves and increasing the postharvest durability.…”
Section: Reducing and Total Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cut flowers, the carbohydrate reserves may increase the longevity potential of the flowers (Mattos et al, 2018). For some species, the carbohydrates present in the flower can support an increase in postharvest durability of the flower, while in other species; they are not enough to supply the metabolism of the flowering stems after cutting (Costa et al, 2021). Thus, the maintenance of the sugar content in the Red Torch ginger inflorescences coated with 6% starch compared to the other treatments (0, 2%, 4%) shows the efficiency of this coating in delaying the consumption of reserves and increasing the postharvest durability.…”
Section: Reducing and Total Sugarsmentioning
confidence: 99%
“…Postharvest quality is related to the maintenance of plant metabolism and delayed senescence, so its improvement requires an analysis of physiological and biochemical aspects (Costa et al, 2021;Favero et al, 2020). To increase the durability of cut flowers, postharvest technologies such as films on the surface of the product and modification of the atmosphere around it have been used.…”
Section: Introductionmentioning
confidence: 99%
“…In evaluating harvest points of sunflower 'Sunbright Supreme', Nascimento et al ( 2019) also observed that stems harvested while still closed showed greater commercial durability. The greater longevity observed in stems harvested in R4 is a consequence of the greater potential for water absorption, retention, and transport in stem tissues, characteristics that have been pointed out as effective for obtaining greater postharvest durability of cut flowers (Nascimento et al, 2019;Costa et al, 2021).…”
Section: /7mentioning
confidence: 99%
“…Cut flower quality and post-harvest longevity depend on factors such as handling, environment, stage of development, hormonal balance, carbohydrate content, and the water relations that constitute one of the main factors that play a critical role in regulating cut flower senescence (Costa et al, 2021). The stage of development of cut flowers directly influences the total durability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation